Possible neurotoxicity of the anesthetic propofol: evidence for the inhibition of complex II of the respiratory chain in area CA3 of rat hippocampal slices - Berndt, Nikolaus; Kann, Oliver (Archives of toxicology, 2018)
Propofol is the most frequently used intravenous anesthetic for induction and maintenance of anesthesia. Propofol acts first and formost as a GABAA-agonist, but effects on other neuronal receptors and voltage-gated ion channels have been described. Besides its direct effect on neurotransmission, propofol-dependent impairment of mitochondrial function in neurons has been suggested to be responsible for neurotoxicity and postoperative brain dysfunction. To clarify the potential neurotoxic effect in more detail, we investigated the effects of propofol on neuronal energy metabolism of hippocampal slices of the stratum pyramidale of area CA3 at different activity states. We combined oxygen-measurements, electrophysiology and flavin adenine dinucleotide (FAD)-imaging with computational modeling to uncover molecular targets in mitochondrial energy metabolism that are directly inhibited by propofol. We found that high concentrations of propofol (100 µM) significantly decrease population spikes, paired pulse ratio, the cerebral metabolic rate of oxygen consumption (CMRO2), frequency and power of gamma oscillations and increase FAD-oxidation. Model-based simulation of mitochondrial FAD redox state at inhibition of different respiratory chain (RC) complexes and the pyruvate-dehydrogenase show that the alterations in FAD-autofluorescence during propofol administration can be explained with a strong direct inhibition of the complex II (cxII) of the RC. While this inhibition may not affect ATP availability under normal conditions, it may have an impact at high energy demand. Our data support the notion that propofol may lead to neurotoxicity and neuronal dysfunction by directly affecting the energy metabolism in neurons.
Gesehen am 29.07.2019
Im Titel ist die 3 in CA3 tiefgestellt